The Mouse Genome Database (MGD). A comprehensive public resource of genetic, phenotypic and genomic data. The Mouse Genome Informatics Group. - Blake, J A (1997)
The Mouse Genome Database (MGD) is a comprehensive community resource of mouse genetic and biological information populated both with data from published literature and with data electronically submitted from the research community. MGD stores genetic, physical and comparative mapping data, clones/probes/PCR information, and phenotype descriptions for genes, mutations and mouse strains. Supporting software for importation, analysis, display and distribution of mouse genetic data have been developed. User support is provided through dedicated staff providing documentation, training, and response to individual user queries. MGD is accessible over the Internet at URL http://www.informatics.jax.org.